The transcriptional co-activator Yap1 promotes adult hippocampal neural stem cell activation - Fan, Wenqiang; Jurado-Arjona, Jerónimo; Alanis-Lobato, Gregorio; Péron, Sophie; Berger, Christian; Andrade-Navarro, Miguel A.; Falk, Sven; Berninger, Benedikt (EMBO Journal, 2023)
Most adult hippocampal neural stem cells (NSCs) remain quiescent, with only a minor portion undergoing active proliferation and neurogenesis. The molecular mechanisms that trigger the transition from quiescence to activation are still poorly understood. Here, we found the activity of the transcriptional co-activator Yap1 to be enriched in active NSCs. Genetic deletion of Yap1 led to a significant reduction in the relative proportion of active NSCs, supporting a physiological role of Yap1 in regulating the transition from quiescence to activation. Overexpression of wild-type Yap1 in adult NSCs did not induce NSC activation, suggesting tight upstream control mechanisms, but overexpression of a gain-of-function mutant (Yap1-5SA) elicited cell cycle entry in NSCs and hilar astrocytes. Consistent with a role of Yap1 in NSC activation, single cell RNA sequencing revealed a partial induction of an activated NSC gene expression program. Furthermore, Yap1-5SA expression also induced expression of Taz and other key components of the Yap/Taz regulon that were previously identified in glioblastoma stem cell-like cells. Consequently, dysregulated Yap1 activity led to repression of hippocampal neurogenesis, aberrant cell differentiation, and partial acquisition of a glioblastoma stem cell-like signature.
CRIS-Team Scopus Importer:2023-05-05
Keywords: hippocampus; neurogenesis; quiescence; radial glia; single cell RNA sequencing